Cardiac and cerebrovascular complications and bleeding in head and neck cancer - Haapio, Eeva (fi=Turun yliopisto|en=University of Turku|, 2018)
In head and neck surgery, there is generally a 1–1.5% risk of cardiac and cerebrovascular complications. However, risk of these events in head and neck cancer surgery is less well established. Smoking and heavy alcohol consumption increase the risk of head and neck cancer, and they are also significant risk factors of cardiac and cerebrovascular comorbidity. There is evidence that age and comorbidity in general increase the risk of major adverse cardiac and cerebrovascular events (MACCE), but the effect of specific comordities remains unknown. Furthermore, it would be useful to identify modifiable peri- and postoperative variables in order to decrease the risk of MACCE. This thesis sought to assess the incidence of MACCE and means to predict adverse events during and after head and neck surgery. Secondly, specific comorbidities and modifiable peri- and postoperative risk factors influencing MACCE risk were identified. This retrospective study included all head and neck patients treated in Turku University Hospital in 1999-2008 (n=456). Data was collected from patient files. Results of this study support the data that increasing age and comorbidities play a significant role in MACCE, and there is an unmet need for a good predictive tool to assess patients at high risk of MACCE. ASA-classification and CHA2DS2-VASc score seemed to predict the risk of postoperative 30-day MACCE. and the easy-to-use CHA2DS2-VASc score could be used by the multidisciplinary team to estimate patients’ peri- and postoperative risk of MACCE. Futhermore, excessive fluid administration exceeding 4000mL/24h and red blood cell infusion increased the risk of 30-day MACCE nearly 5- fold. Other peri- and postoperative risk factors were microvascular surgery, treatment in the intensive care unit, and tracheostomy, all referring to major surgery. Nevertheless, MACCE also occurred in minor head and neck surgery. However, re-operation due to bleeding did not increase the risk of MACCE, but increased the risk of 30-day mortality more than 5-fold, and in all cases the cause of death was cardiovascular. By addressing the high-risk patients and controlling the known modifiable risk factors, we might be able to decrease morbidity and mortality due to MACCE in head and neck cancer surgery in the future. For example, and the easy-to-use CHA2DS2-VASc score could be used by the multidisciplinary team to estimate patients’ peri- and postoperative risk of MACCE.